Weak Magnetic Fields in the Outer Solar Nebula Recorded in CR Chondrites. Issue 5 (8th May 2020) - Fu, Roger R.; Kehayias, Pauli; Weiss, Benjamin P.; Schrader, Devin L.; Bai, Xue‐Ning; Simon, Jacob B.
Abstract: Theoretical investigations suggest that magnetic fields may have played an important role in driving rapid stellar accretion rates and efficient planet formation in protoplanetary disks. Experimental constraints on magnetic field strengths throughout the solar nebula can test the occurrence of magnetically driven disk accretion and the effect of magnetic fields on planetary accretion. Here we conduct paleomagnetic experiments on chondrule samples from primitive CR (Renazzo type) chondrites GRA 95229 and LAP 02342, which likely originated in the outer solar system between 3 and 7 AU approximately 3.7 million years after calcium aluminum‐rich inclusion formation. By extracting and analyzing 18 chondrule subsamples that contain primary, igneous ferromagnetic minerals, we show that CR chondrules carry internally non‐unidirectional magnetization that requires formation in a nebular magnetic field of ≤8.0 ± 4.3 μT (2 σ ). These weak magnetic fields may be due to the secular decay of nebular magnetic fields by 3.7 million years after calcium aluminum‐rich inclusions, spatial heterogeneities in the nebular magnetic field, or a combination of both effects. The possible inferred existence of spatial variations in the nebular magnetic field would be consistent with a prominent role for disk magnetism in the formation of density structures leading to gaps and planet formation. Plain Language Summary: Stars and their planetary systems form from large, flattened structures composed of low‐density gas and dust called protoplanetary disks. Two major unresolved questions regarding protoplanetary disks are the mechanisms that limit their lifetimes to a few million years and the mechanisms that create the first planets from dust particles. Turbulence in the gas caused by action of magnetic fields have been hypothesized as explanations for both of these processes. In our study, we measure the permanent magnetization of 1 mm‐sized inclusions from two meteorites called GRA 95229 and LAP 02342. These inclusions are believed to have formed 3.7 Ma after the formation of the protoplanetary disk around the Sun and beyond about 3 astronomical units (AU) from the Sun (1 astronomical unit is the Earth‐Sun distance equal to 150 × 10 6 km). We find that the inclusions formed in a magnetic field of ≤8 μT, a fraction of the surface magnetic field on Earth and lower than expected from previous measurements in the protoplanetary disk closer to the Sun. This potentially provides evidence for heterogeneities in the nebular gas, which may be the locations of planet formation or partial dissipation of the disk in 3.7 million years. Key Points: Paleomagnetic measurements of carbonaceous chondrites can provide important constraints on outer solar system magnetic fields Our measurements on primitive CR chondrules show that they formed in a magnetic field ≤8 μT Such low fields suggest either spatial variations in the nebular magnetic field or incipient dissipation of the nebula by 3.7 Myr after CAIs